Association Between Circadian Hemodynamic Characteristics and Target Organ Damage in Patients With Essential Hypertension. (18th June 2019) - Kusunoki, Hiroshi; Iwashima, Yoshio; Kawano, Yuhei; Hayashi, Shin-ichiro; Kishida, Masatsugu; Horio, Takeshi; Shinmura, Ken; Yoshihara, Fumiki
Abstract: BACKGROUND: This study investigated the association between circadian hemodynamic characteristics and asymptomatic hypertensive organ damage. METHODS: Circadian hemodynamics, including 24-hour brachial and aortic systolic blood pressure (SBP), pulse wave velocity (PWV), augmentation index (AIx@75), cardiac index, and total vascular resistance (TVR), were evaluated using an oscillometric device, Mobil-O-Graph, in 284 essential hypertensive patients (67.8 ± 16.0 years, 54% female). Hypertensive target organ damage (TOD), namely carotid wall thickening, left ventricular hypertrophy, and albuminuria, was assessed in all patients. RESULTS: Office SBP and 24-hour brachial and aortic SBP all increased with increasing number of organs involved (all P < 0.01 for trend). After multivariate logistic regression analysis, 24-hour brachial SBP (odds ratio [OR] = 1.04 for 1 mm Hg increase, P < 0.001) as well as aortic SBP (OR = 1.03 for 1 mm Hg increase, P < 0.05) maintained significance. Percent decrease during nighttime in brachial SBP, PWV, and TVR, but not cardiac index, showed a significant graded relationship with the number of organs involved. In a multivariate stepwise regression model, the nighttime values of brachial SBP, PWV, and TVR emerged as independent predictors of the presence of TOD. CONCLUSION: In essential hypertension, 24-hour aortic SBP could be a marker of subclinical TOD, and further, the blunted nocturnal BP reduction in TOD patients might be mediated by disturbed circadian hemodynamic variations in aortic SBP, vascular resistance, and arterial stiffness.